1992
DOI: 10.1159/000211032
|View full text |Cite
|
Sign up to set email alerts
|

Topical and Systemic Absorption of Sodium Pyrithione following Topical Application to the Nails of the Rhesus Monkey

Abstract: A study was performed to investigate the local penetration into the nail, the systemic absorption into the rest of the body, and the routes of excretion of sodium pyrithione following topical application to the nail. Approximately 20 µ1 of a film-forming 3% sodium 14C-pyrithione solution was applied once daily to 5 fingernails and 5 toenails of 4 rhesus monkeys for 6 or 7 days. Following dose removal on study day 7, 2 animals were sacrificed, and the treated nails were analyzed for radioactivity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The significance of this is mainly with respect to inclusion of circulating materials into the nail rather than the other way around, although in a study of topical application of sodium pyrithone, Mayer et al . [225] found microscopic amounts in the systemic circulation. Munro and Shuster [226] and Matthieu et al .…”
Section: Physical Properties Of Nailsmentioning
confidence: 99%
“…The significance of this is mainly with respect to inclusion of circulating materials into the nail rather than the other way around, although in a study of topical application of sodium pyrithone, Mayer et al . [225] found microscopic amounts in the systemic circulation. Munro and Shuster [226] and Matthieu et al .…”
Section: Physical Properties Of Nailsmentioning
confidence: 99%
“…The antifungal drugs were BFZ, a typical topical drug for tinea pedis; AMF, a topical drug for tinea unguium; TBF, an oral drug for tinea unguium; and NaPT, which has good nail penetration. 22 When colony area was used as a measure, the BFZtreated group was found to have improved slightly on the 14th day of drug application, the end point of the evaluation. However, the area of the colony was almost the same as that in the control and vehicle-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…This result supports those of Mayer et al on the pharmacokinetics of topical application of NaPT to the nails of rhesus monkeys. 22 Therefore, our model is suitable for evaluating the antifungal activity, including the pharmacokinetics, of an agent in nail tissue. Moreover, the topical antifungal drug for tinea unguium selected using this model should be considered for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is thought to be responsible for the increase in the 24-hour period. It has been reported that 85-95% of sodium pyrithione exposure in rats is metabolized and excreted in the urine within 4 days at all dosage levels (Mayer et al, 1992). It can be said that this may be the reason why ACTH and corticosterone levels returned to normal within 96 hours.…”
Section: Findings Of Acth Hormone Levels In Rats Treated With Acute P...mentioning
confidence: 99%